Cycle-to-Cycle Variation of the Combustion Process in a Diesel Engine Fueled with Rapeseed Oil—Diethyl Ether Blends - Krzysztof Górski; Ruslans Smigins; Jonas Matijošius; Dimitrios Tziourtzioumis (Energies, 2023)
The application of rapeseed oil (RO) blends with diesel fuel and/or alcohols and/or ethers is known to significantly affect the combustion process. Aiming to further investigate the effects of rapeseed oil in a blend with diethyl ether (DEE) on this process, the coefficient of variation of the mean indicated pressure (COVMIP) of a 2.5l direct injection diesel engine was calculated. The analysis of the experimental results revealed the repeatability of the combustion process variability of diesel fuel (DF), rapeseed oil (RO), and DEE/RO blends containing up to 20% DEE. In these cases, the COVMIP does not exceed 4%. Additionally, it became obvious that for a higher content of DEE in blend with RO, the cyclic repeatability of the mean indicated pressure (MIP) was reduced. Thus, the values of COVMIP for fuels containing 30 and 40% of DEE by vol. in blend with RO were even three times higher than the values obtained for the reference fuel i.e., DF. The results indicate that the increased content of DEE in the mixture with RO is disadvantageous as it leads to excessive unevenness of the engine operation compared to its fueling with DF. The observed deterioration of the combustion process is caused by the vapor locks, which are formed due to the evaporation of volatile DEE in the fuel line, leading to the interrupted operation of the fuel injector.